Nauczanie kultury osobistej w ramach nauczania religii muzułmańskiej w rządowych szkołach podstawowych we współczesnym Egipcie - Wolny, Edyta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Egyptian textbooks concerning Islamic education are a mine of knowledge about how a perfect Egyptian should behave. The textbooks do not only teach religion, but also good behaviour, manners, the appropriate treatment of Christians, taking care of the environment and patriotism. The teaching of manners, good behaviour and co-existence with other people stems from the religion, and it is an important element of religious education in Egyptian primary schools. Islam is a religion of cleanliness, therefore caring about one’s personal hygiene as well as the cleanliness of the home and environment are all very important. This religion calls for good manners and behaviour, honesty, the appropriate treatment of the elderly and young, concern for relatives, co-religionists and Christians. Those areas of the textbooks focussed on good behaviour are supported by relevant quotations from the Quran or Hadith. Many stories inform students that good behaviour is favoured by God. Exercises summarizing the knowledge of each chapter include not only questions about the dogmas, rituals or the history of Islam, but also confront pupils with exercises that examine their knowledge of good manners. Bad behaviour is not only a failure towards society, teachers or parents. It is also a crime against religion. Egypt, repeatedly mentioned in the Quran, and according to the authors of the textbooks, is a special place on Earth.
Keywords: Egypt; Islam; manners; primary school; religion; teaching